Social Media Engagement and Identity: The Loneliness and FOMO Experience of Young People - Dominika Doktorová; Souad El Mghari; Miroslava Tokovská (Communication Today, 2025)
Social media platforms, designed to facilitate connectivity, have a complex impact on psychological well-being. This study investigates the relationship between social media usage, loneliness, and the fear of missing out among young people in Slovakia, focusing on gender differences. Using a quantitative cross-sectional design, data was collected from 225 university students (70.2% female, 29.8% male) through the UCLA Loneliness Scale, the Social Media Engagement Questionnaire (SMEQ), and the Fear of Missing Out (FOMO) Scale. Statistical analyses conducted included linear regression and correlation analyses; the results showed no significant correlation between social media use and loneliness (r = 0.08, p = 0.11), although a weak to moderately strong positive correlation was found between loneliness in women and FOMO (r = 0.24, p = 0.001). Additionally, a significant positive correlation was identified between FOMO and social media use (r = 0.27, p < 0.001), with FOMO predicting increased social media engagement. The study concludes that while social media use does not directly predict loneliness, FOMO significantly influences social media engagement among young people. These findings underscore the importance of considering psychological factors like FOMO in understanding students’ social media behaviour and point to the need for gender-specific approaches to digital wellness.